GE_GERICHTE C/26273/2019 vom 15. November 2022 - GE Cour de justice (2022)
ACTION EN PAIEMENT D'ENTRETIEN;AUTORITÉ PARENTALE;DOMICILE;RELATIONS PERSONNELLES;OBLIGATION D'ENTRETIEN;ENFANT;REVENU HYPOTHÉTIQUE | CC.273; CC.276; CC.279; CC.285; CC.296.al2; CC.301.leta